A new species of Sarcophaga Meigen subgenus Hoa Rohdendorf (Diptera: Sarcophagidae) - Wang, Chao; Xue, Wan-Qi; Zhang, Dong; Pape, Thomas (Zootaxa, 2020)
Sarcophaga (Hoa) membranijuxta sp. nov. is described from the Chinese provinces Guangxi and Hainan and documented with illustrations, photographs and scanning electron microscopy images. The habitus and male terminalia of Sarcophaga (Hoa) basiseta Baranov, 1931 are documented with photographs for the first time, and the circumscription and distribution of the subgenus Hoa Rohdendorf, 1937 are updated.